Demographic, Clinical and Laboratory Characteristics of Ocular Syphilis: 6-Years Case Series Study From an Eye Center in East-China - Sun, Chuan-bin; Liu, Geng-hao; Wu, Rong; Liu, Zhe (Frontiers in Immunology, 2022)
Purpose: To report the demographic, clinical and laboratory characteristics of ocular syphilis based on 6-years case series study from an eye center in East-China. Methods: One hundred and thirty one cases (191 eyes) of ocular syphilis, and annual number of total syphilis cases from January, 2016 to December, 2021 were included in this study. Detailed medical records including systemic and ophthalmic medical history, complete ophthalmic examination, colour fundus photography, B-type ultrasound, fundus fluorescein angiography (FFA), spectral domain optical coherence tomography (SD-OCT), laboratory tests of the serum and cerebrospinal fluid (CSF) samples, as well as visual field test and orbital or cranial MRI in cases with suspected optic neuritis or atrophy, were collected and analyzed. Pearson Chi-square or Fisher’s exact tests was used for statistics analysis. Results: Of 131 cases with ocular syphilis, 86 cases were male, 6 cases had a past medical history or systemic manifestation of syphilis. HIV was found only in 2 of 70 cases undergoing serum HIV test. The average age was 54.0 years, ranged from 26 to 85 years. The average percentage of ocular syphilis out of total syphilis cases was 5.1%, the average titer of serum rapid plasma regain (RPR) at presentation was 1:32, ranged from 1:1 to 1:512.The most predominant manifestation of ocular syphilis was posterior uveitis, followed by optic neuritis, optic atrophy, panuveitis, retinal vasculitis, and retinitis. The median of BCVA of all 191 eyes was 20/200 (ranged from no light perception to 20/20), and 20/40 (ranged from no light perception to 20/20) at presentation and final follow-up, respectively. Ocular syphilis with active inflammation responded well to penicillin therapy, no matter what the initial visual acuity, ocular disease type, and RPR titers were, as long as it was diagnosed early and treated properly and promptly. However, cases with optic atrophy, acute retinal necrosis, late diagnosis, permanent disruption or loss of outer segment of photoreceptors of macular retina on SD-OCT showed poor visual improvement after therapy. Conclusions: Early diagnosis of ocular syphilis is still challenging in clinical practice, syphilis test should be routinely performed in patients with uveitis, retinitis, optic neuritis, and optic atrophy